Validación de la escala de sensibilidad intercultural de Chen y Starosta con estudiantes ecuatorianos de secundaria (Investigaciones) - Quishpe Guano, Enoc Felipe (2025)
Schools are spaces of social interaction where individuals from diverse backgrounds converge, making it essential to develop social competencies—among them, intercultural sensitivity—to foster respectful and peaceful coexistence. In this regard, it is necessary to have instruments that allow the measurement of students’ levels of intercultural sensitivity. This study aims to adapt the Intercultural Sensitivity Scale (ISS) developed by Chen and Starosta to the Ecuadorian context and to assess its validity and reliability among secondary school students through confirmatory factor analysis. For the validation process, the ISS—translated and culturally adapted—was administered to 5,497 students. Cronbach’s alpha indicated acceptable internal consistency (α = 0.856); however, the CFI and RMSEA indices suggested the need to adjust the model to better fit the national context. Several items exhibited low factor loadings (λ < 0.4), suggesting they should be reviewed or removed to enhance the representation of latent variables. Additionally, strong correlations were found between some factors, such as Respect and Engagement, while others, such as Attention and Enjoyment, showed weak correlations, indicating that they capture more specific aspects of the broader construct. After adjustments, the scale can be considered culturally adapted and validated for assessing intercultural sensitivity among Ecuadorian adolescents.